Contemporary Matters of Constitutionalization of Legal Norms in the Republic of Armenia - Davtyan, Narine (Bulletin of Yerevan University C: Jurisprudence, 2023)
The article examines the issues of constitutionalization of law in RA.The constitutionalization of the right is one of the contemporary problems of modern constitutionalism, which is currently of interest not only to specialists in the field of constitutional law but also to scholars dealing with problematic issues in other branches of law, the article studied the Constitutionalization process, which is of great importance in terms of guaranteeing the supremacy of the Constitution and is meant to ensure the compliance of normative legal acts with the requirements of the Constitution.The process of constitutionalization was studied from an institutional point of view, conventionally classifying it into two main groups.First, it is the units operating in the field of public service which is entitled to subject the drafts of normative legal acts to legal examination. One of the important goals of such examination is to provide law-making bodies and officials with conclusions on the conformity of the legal acts reflected in the drafts of the aforementioned normative legal act with the requirements of the Constitution.Second, as a result of the constitutional reforms of 2015, the role and importance assigned to the Constitutional Court in order to ensure the constitutionalization of the legal fiel was studied. The Constitutional Court, as a constitutional supervisory body, is called to ensure the supremacy of the Constitution, which is carried out within the framework of concrete and discrete control.
Keywords: constitutionalization of law; supremacy of the Constitution; process of constitutionalization; legal examination